Navigating Hepatocellular Carcinoma Treatment in the Context of Frailty - Rabei, Rana; Fidelman, Nicholas (Medical Research Archives, 2023)
The aim of this review is to explore the implications of frailty in the treatment of patients with hepatocellular carcinoma (HCC). Frailty, a multidimensional geriatric syndrome, has been increasingly recognized as an important predictor of adverse outcomes and mortality in various patient populations. This review specifically focuses on the prevalence of frailty in the cirrhotic population and its role as a prognostic tool for procedural and surgical outcomes of transplantation, hepatectomy and liver-directed therapies. Understanding the impact of frailty on HCC treatment can help guide clinicians in optimizing management strategies and improving patient outcomes.